Augmented flow and reduced clogging of particles passing through small apertures by addition of fine grains - Gharat, Sandip (2023)
The effect on the flow and clogging of a sample of particles passing through an orifice due to the addition of a second fine-graded species is investigated. The flow rate of the main species is measured for various parameters: the mass ratio of the big species, the particle size ratio and the orifice diameter. We show that when the fine grains are added into the system the flow rate of the larger species can be increased and its clogging significantly reduced. In particular, we were able to flow (without clogging) the big species through an orifice only 1.5 times its particle diameter. This allows for applications such as the alignment of particles in a narrow tube without clogging. A simple state diagram is presented to describe the clogging transition for these binary mixtures. The experimental results are compared with various existing models for the flow rate of binary mixtures.